Educational Evaluation: A Simple Additive Weighting Approach For Decision-Making In Transformational Leadership Development Systems - Komalasari, Yeti; Abdullah, Anton; Agung Ayu Mas Oka, I Gusti; Masito, Fitri; Badeni, Badeni; Kristiawan, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study uses the weighting approach to evaluate decision-making strategies in order to rank the importance of the traits that a leader must have in order for the Cadet Regiment Commander to create a transformational leadership model. A decision support system's weighted sum or simple weighting method can be applied to issue solving through the use of Simple Additive Weighting (SAW). This kind of research is called mixed method, since it uses a survey methodology along with qualitative and descriptive quantitative research methods. The author, who is actively engaged in the research, is the research instrument in and of himself. The purpose of this study is to determine the respondents by means of a purposive technique, in which information for research objectives will only come from specific individuals or parties. The study's findings should determine which leader qualities are most important for creating a transformational leadership model. This will be done by applying the SAW method, which is based on five weighting criteria for transformational leadership: motivation and traits, knowledge, skills, and abilities, organizational culture, vision, and vision implementation. Of the five characteristics of the leader, motivation and traits are the criteria that are the top priority to be developed based on the respondents' assessment with a value of 22.3%. Where a leader must have the ability to achieve, ambition, persistence, passion, initiative, have leadership motivation and have the values of honesty/integrity, confidence, originality, creativity and flexibility/adaptability needed to set an example, encourage and motivate other cadets towards achieving the vision of the organization. Followed by weighting on other criteria such as knowledge, skills, and abilities at 20.5%, organizational culture at 18.8%, vision at 19.5%, and vision implementation at 18.9%.